"So Many Open Doors?": An Examination of Gender Stereotypes in State Judicial Campaign Advertisements. (1st October 2016) - Walsh, Mary; Walker, Teri; Patterson, Brian; Hardy, Phillip
ABSTRACT: In the present study we examine gender stereotyping in the traits and images emphasized by candidates in state judicial campaigns. Content analyses were conducted on televised campaign advertisements from state supreme court contests in election years 2008–2010. Our analyses indicate that women referenced masculine traits and were shown with masculine images in their ads more than men. In addition, the gender makeup of the race made a difference; when running against a man, women stress intelligence and being hardworking more than men. Conversely, women mentioned experience to a high degree when running against other women.